PENGEMBANGAN KAWASAN WISATA AIR DI PULAU TIDUNG, KEPULAUAN SERIBU - Apriyanti, Rehulina (Jurnal Ilmiah Desain & Konstruksi, 2014)
The development of the tourist area on the island tidung is a step to be able to improve tourist facilities existing in Tidung Island. Tidung island as a mainstay in the tourist area of the Thousand Islands is currently a resident of Jakarta tourist destination. With the increasing number of tourists to the island Tidung it is necessary to the development of the region in accordance with the existing potential in Tidung itself. Development of water in the tourist area Tidung a solution to be able to reorganize the region Tidung which has the natural beauty of the beauty of the sea and its contents. Key Words: Seribu archipelago, Development, Tidung Island, Water tourism